PHYSICAL GROWTH OF STUDENTS BETWEEN 11 AND 15 YEARS OLD FROM ELEMENTARY SCHOOL FROM THE MUNICIPAL DISTRICT OF MARECHAL CÂNDIDO RONDON PR. (Fiep Bulletin - online, 2015)
The adolescence is a period of extreme transformations. It's marked for its increasing of weight and height, because in this period there are some phenomena as that one called puberty. This study had the purpose of analyzing the physical growth of students from elementary school from the Municipal district of Marechal Cândido Rondon  PR. The sample is composed of 731 people, from these, 370 are male and 361 are female. This research involved facts that tried to bring out the characteristics of the students' physical growth, as: sex, age, height, weight and their parents' height. To collect the dates, we used the procedures described by PETROSKI( 1999) and the form of the genetic target was from LONGUI (1996). The results showed a tendency of normality when compared to those references found in the literature. And for the genetic target there were found many valuers apparently higher than the potential waited. It can be also said that the environment is propitious to the physical growth or that some ethnic mixtures happened, which has turned the growth less influenceable to the outside facts.
Keywords: genetic target; adolescence; fast growth.